Pengaruh Pemanasan Bahan Bakar dan Penambahan Biodiesel dalam Solar terhadap Opasitas Mesin Diesel Mitsubishi L300 - Diki Cahyo Gumilang; Danar Susilo Wijayanto; Husin Bugis (Universitas Janabadra, 2016)
The purpose of this research is to: (1) investigate the effect of fuel heating through spiral-fin pipes in the radiator upper tank towards exhaust gases opacity of Mitsubishi L300 Diesel Engine. (2) investigate the effect of biodiesel adding into diesel fuel towards exhaust gases opacity of Mitsubishi L300 Diesel Engine. (3) investigate the effect of fuel heating through spiral-fin pipes in the radiator upper tank and biodiesel adding into diesel fuel towards exhaust gases opacity of Mitsubishi L300 Diesel Engine. (4) investigate the best result beetwen fuel heating through spiral-fin pipes in the radiator upper tank and biodiesel adding into diesel fuel towards exhaust gases opacity of Mitsubishi L300 Diesel Engine. This research was a quantitative with experiments methods. The result of this reserach is: (1) Fuel heating decreased opacity level of Mitsubishi L300 diesel engine. The largest decrease of opacity level occured on fuel heating using spiral fin pipes with 6 spiral threads 44,175 (%). (2) The addition of biodiesel into diesel fuel decreared opacity level of Mitsubishi L300 diesel engine. The best opacity level occured in addition the mix of 30% biodiesel and 70% diesel fuel 39,025 (%). (3) Fuel heating and addition at biodiesel in diesel fuel decreased opacity level in Mitsubishi L300 diesel engine. The largest decrease of opacity level occured at 30% biodiesel and 70% diesel fuel level and fuel heating used the spiral fin pipes with 2 spiral thread 34,4 (%).